2008
DOI: 10.1128/mcb.00055-08
|View full text |Cite
|
Sign up to set email alerts
|

Pseudosubstrate Inhibition of the Anaphase-Promoting Complex by Acm1: Regulation by Proteolysis and Cdc28 Phosphorylation

Abstract: The ubiquitin ligase activity of the anaphase-promoting complex (APC)/cyclosome needs to be tightly regulated for proper cell cycle progression. Substrates are recruited to the APC by the Cdc20 and Cdh1 accessory proteins. The Cdh1-APC interaction is inhibited through phosphorylation of Cdh1 by Cdc28, the major cyclin-dependent protein kinase in budding yeast. More recently, Acm1 was reported to be a Cdh1-binding and -inhibitory protein in budding yeast. We found that although Acm1 is an unstable protein and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(71 citation statements)
references
References 74 publications
(108 reference statements)
6
65
0
Order By: Relevance
“…The APC coactivator Cdh1, which is involved in the recruitment of target substrates to the APC, is inhibited from binding its targets by Cdc28-dependent stabilization of Acm1. 69 TOS4, MCD1, SWE1 and ACM1 are cell cycle-regulated, and, corroborating our hypothesis that switch genes expression needs to be tightly regulated, overexpression of these genes was linked to growth defect and/or cell cycle arrest. 65,66 Further analysis of the other switch genes, such as the TOS genes and eight putative ORFs, will show their potential role as checkpoint effectors.…”
Section: "Switch Genes:" a New Class Of G 1 /S Cell Cycle Genessupporting
confidence: 86%
“…The APC coactivator Cdh1, which is involved in the recruitment of target substrates to the APC, is inhibited from binding its targets by Cdc28-dependent stabilization of Acm1. 69 TOS4, MCD1, SWE1 and ACM1 are cell cycle-regulated, and, corroborating our hypothesis that switch genes expression needs to be tightly regulated, overexpression of these genes was linked to growth defect and/or cell cycle arrest. 65,66 Further analysis of the other switch genes, such as the TOS genes and eight putative ORFs, will show their potential role as checkpoint effectors.…”
Section: "Switch Genes:" a New Class Of G 1 /S Cell Cycle Genessupporting
confidence: 86%
“…16 Conditions were identical to those under which we observed the spindle defects in Figure 1. Acm1 has been shown to block the binding of Clb2 and Hsl1 to Cdh1, 7,9,10,22 and ubiquitination of several of these substrates by APC Cdh1 is inhibited by Acm1 in vitro. 7,9,22 However, our results here argue that Acm1 is not required for APC Cdh1 inhibition in vivo, even in anaphase, when Cdk activity has been lowered by cyclin degradation.…”
Section: Resultsmentioning
confidence: 99%
“…Acm1 has been shown to block the binding of Clb2 and Hsl1 to Cdh1, 7,9,10,22 and ubiquitination of several of these substrates by APC Cdh1 is inhibited by Acm1 in vitro. 7,9,22 However, our results here argue that Acm1 is not required for APC Cdh1 inhibition in vivo, even in anaphase, when Cdk activity has been lowered by cyclin degradation. 23 It was previously suggested that Acm1's pseudosubstrate properties could be important for preventing inappropriate Cdh1-substrate interactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In animals, Emi1 is an E2F transcriptional target, which binds and inhibits Cdh1 [48]; in yeast, Acm1 similarly binds and inhibits Cdh1 [49] and is expressed specifically at G1-S, probably under SBF control [50]. However, Acm1 and Emi1 lack detectable sequence similarity [51]. Sic1 and Kip-Cip are both tight-binding stoichiometric inhibitors of cyclin-Cdk complexes, and Cdk1 phosphorylation targets both Sic1 and Kip for degradation via the SCF complexes ubiquitin ligase.…”
Section: The G1 -S Regulatory Network In Budding Yeast and Animals Hamentioning
confidence: 99%